2020
DOI: 10.21203/rs.3.rs-33553/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exosome-based biomimetic nanoparticles targeted to inflamed joints for enhanced treatment of rheumatoid arthritis

Abstract: Backgroud: Glucocorticoids (GCs) show powerful treatment effect on rheumatoid arthritis (RA). However, the clinical application is limited by their nonspecific distribution after systemic administration and serious adverse reactions during long-term administration. To achieve better treatment and reduce side effect, we here established a biomimetic exosome (Exo) encapsulating dexamethasone sodium phosphate (Dex) nanoparticle (Exo/Dex), whose surface was modified with folic acid (FA)-polyethylene glycol (PEG)-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Yan et al reported a platform of RAW 264.7-derived EVs coupled with FA-bearing polyethylene glycol (PEG)-cholesterol (Chol) to encapsulate and control the delivery of dexamethasone (Dex), which is the most frequently used glucocorticoids to treat RA in the clinic. Dex can downregulate pro-inflammatory cytokines of macrophages 183 . The incorporation of Dex into EVs was achieved by electroporation.…”
Section: Engineering Advanced Therapeutic Strategies In Treating Oa and Cartilage Injurymentioning
confidence: 99%
“…Yan et al reported a platform of RAW 264.7-derived EVs coupled with FA-bearing polyethylene glycol (PEG)-cholesterol (Chol) to encapsulate and control the delivery of dexamethasone (Dex), which is the most frequently used glucocorticoids to treat RA in the clinic. Dex can downregulate pro-inflammatory cytokines of macrophages 183 . The incorporation of Dex into EVs was achieved by electroporation.…”
Section: Engineering Advanced Therapeutic Strategies In Treating Oa and Cartilage Injurymentioning
confidence: 99%
“…They are very unstable when dissolved in water molecules; therefore, the product's shelf life is quite short. Inorganic nanoparticles are very unstable, have significant biological toxicity, and have a poor targeting impact (Yan et al 2020 ).…”
Section: Herbal Medicines and Natural Products Nanocarriers Explored ...mentioning
confidence: 99%
“…After staining the cell nuclei with DAPI, endocytosis was observed by confocal laser scanning microscopy (Leica Microsystems, Wetzlar, Germany) [37]. Uptake of the labeled formulations was also observed by ow cytometry using a Verse cytometer (BD Biosciences, Franklin Lakes, NJ, USA) after stimulating RAW264.7 cells for 24 h with LPS.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…RA severity was evaluated by rating the paw swelling according to the following scale [37]: 0, no signs of swelling; 1, mild in ammation and swelling of individual toes; 2, moderate in ammation and swelling of all toes; 3, severe swelling of the entire paw; and 4, maximum swelling of the limb. The scores of each paw were summed to calculate the total arthritis index score for the animal.…”
Section: Hemolysis Assaymentioning
confidence: 99%
See 1 more Smart Citation